Recent Irish and British migration to Berlin. A case of lifestyle migration? - Neumann, Melanie (WVT, Wissenschaftlicher Verl., 2020)
This book offers a detailed insight into the Irish and British communities in Berlin. It examines the causes and effects of these migration flows: What motivates the Irish and British to come to Berlin? How do they contribute to the city’s cultural life and labour market? To what extent do the migrants feel they belong in the host society? In what way do they contribute to inequality and exclusion and to what extent are they themselves caught up in it? What role does language play – can English be seen as a form of cultural capital or does it lead to discrimination? What is the significance of German? Additionally, the impact of Brexit on Britons in the sample as well as the recovery of the Irish economy on the Irish respondents is highlighted. The presented research furthermore tests whether the recent increase in these two migration flows can be connected to lifestyle migration. At the same time, the lifestyle migration concept itself is subjected to critical scrutiny regarding its general value to migration research. Therefore, this monograph does not only contribute to the development of both lifestyle migration and migration research in general, but further gives a practical insight into a sample group of privileged migrants in a European capital.
Keywords: Stadtsoziologie; Migration; Migrationsanalyse; Wanderungsmotiv; Empirische Untersuchung; Interview; Wohnstandort; Standortattraktivität; Berufstätigkeit; Freizeitaktivität; Kultur; Bevölkerungsgruppe; Zuwanderung; Soziale Integration; Lebensbedingungen; Lebensstil; Lifestyle; Brexit